2010
DOI: 10.1111/j.1582-4934.2009.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel recombinant immunotoxin with the smallest ribosome‐inactivating protein Luffin P1: T‐cell cytotoxicity and prolongation of allograft survival

Abstract: In the creation of stable tolerance to MHC-incompatible allografts, reducing the large mass of donor-reactive cells via apoptosis is often required. Apoptosis induction by immunotoxins targeting surface molecules specifically presented on donor-reactive cytopathic T effector (Teff) cells is a promising strategy. Traditionally, the toxin moieties are bacterial exotoxins or plant-derived ribosome-inactivating proteins (RIPs) with large molecular size and strong immunogenicity, hence causing the problems of tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Vicilins are a family of ubiquitous seed storage proteins, which are translated as preproproteins consisting of three conserved regions: a short, hydrophobic signal peptide that is removed upon location to a storage vacuole; an N-terminal, cysteine-rich leader sequence (LS), which is removed by asparaginyl endopeptidase (AEP); and the mature vicilin domain. Recent studies have identified a new family of peptides, termed vicilin-buried peptides (VBPs) within this LS region. These VBPs are defined by a common cysteine motif (CxxxCx (10–14) CxxxC) and are widely dispersed across most angiosperm families including trees, grasses, nightshades, and legumes, , where they have been implicated in a variety of biological functions including ribosome inactivation, protease inhibition, and antimicrobial defense. Despite this diversity, the structure of all VBPs that have been solved to date reveals a common α-hairpin fold/motif (also called α-hairpinin) mediated by disulfide bonds between the highly conserved CxxxC motifs, potentially providing a common structural scaffold that can mediate peanut/tree nut cross-reactivity. , …”
Section: Introductionmentioning
confidence: 99%
“…Vicilins are a family of ubiquitous seed storage proteins, which are translated as preproproteins consisting of three conserved regions: a short, hydrophobic signal peptide that is removed upon location to a storage vacuole; an N-terminal, cysteine-rich leader sequence (LS), which is removed by asparaginyl endopeptidase (AEP); and the mature vicilin domain. Recent studies have identified a new family of peptides, termed vicilin-buried peptides (VBPs) within this LS region. These VBPs are defined by a common cysteine motif (CxxxCx (10–14) CxxxC) and are widely dispersed across most angiosperm families including trees, grasses, nightshades, and legumes, , where they have been implicated in a variety of biological functions including ribosome inactivation, protease inhibition, and antimicrobial defense. Despite this diversity, the structure of all VBPs that have been solved to date reveals a common α-hairpin fold/motif (also called α-hairpinin) mediated by disulfide bonds between the highly conserved CxxxC motifs, potentially providing a common structural scaffold that can mediate peanut/tree nut cross-reactivity. , …”
Section: Introductionmentioning
confidence: 99%